(3TQM CMcGe GdLfSjI HGdEVGaI Edi CMcGe eMceI GdYOd GdYdjG aj eSGFd GdLfSjI (B/s - (3GdYjhf, bUj eMeOs ((3YeGf, GdCQOf (B:s (3OGQ GdKbGaI ddfTQ hGdJhRjY,s, 2009)
(3jYO bGfhf GdLfSjI ef GdehGVjY GdegeI aj GdbGfhf, abGfhf GdLfSjI gh GdPj jMOO ehGWfj GdOhdI hjMOO cPdc ef ge GdCLGfH(B. (3hJYO GdJaQbI Hjf GdehGWf hGdCLfHj ef GdCehQ GdegeI aGdehGWf dg Mbhb hYdjg hGLHGJ, JNJda Yf Mbhb GdCLfHj hhGLHGJg(B. (3CeG HGdfSHI dcjajI GNJUGU GdOhdI HJfXje eGOI LfSjJgG acd OhdI MQI aj JfXje eGOI LfSjJgG MSH eG JbJVjg eUdMJgG GdYGeI agfGc Ohd eKdG JHfj LfSjJgG Ydi Mb GdOe ef LgI GdCH Ohf GdCe, hJCNP HMb GdEbdje GSJKfGA, hefgG GdeedcI GdCQOfjI GdgGTejI heYXe GdOhd GdYQHjI hgfGc ef GdOhd ef JHfj LfSjJgG HfGA Ydi Mb GdEbdje(B. (3acCUd YGe Ef GdOhdI MQI aj JfXje eGOI LfSjJgG EdG eG jQO YdjgG ef bjhO GJaGbjI, hdG JYJHQ aj GdMbjbI bjhOG dCf GdOhdI GQJVJ HgG WhYG(B. (3haj gPG GdcJGH OQSfG eGOI GdLfSjI GdCQOfjI hCMcGegG aj HGHjf JYQVfG NdGdgeG deYXe ehGVjY GdLfSjI hCMcGegG aj GdbGfhf GdCQOfj(B. (3Bedjf ef Gddg Cf Cchf bO habJ aj Pdc hGddg Gdehab(B. s
(3HHdjhLQGajI (B: (3UaMI (B239-240.s
Keywords: (3GdCQOf(B.s -- (3eMceI GdYOd GdYdjGs; (3GdLfSjIs -- (3bhGfjf hJTQjYGJs -- (3GdCQOfs